Attack Against the HQ of Hungarian State Television — the Realities of the Policemen - Fogarasi, Mihály (Magyar Rendészet, 2016)
The study represents the results of the group-representations of the policemen participated in the 18/09/2006 clash. We created two representative-groups from policemen participated in the clashes of 18/09/2006: one group included policemen who took an active role in the protection of the HQ; the other included policemen-reserves on the scene. We used half-structured interview-technics. The texts were analysed according to the sequential-transformative-model. The groups constructed both different and similar components of social representations concerning the events.